Chediak-Higashi Syndromein Accelerated Phase: A Case Report - Zulfiqar, Maryam; Mustafa, Asma; Ali, Bushra Anam; Naseem, Lubna (International Journal of Pathology, 2018)
Chediak Higachi Syndrome (CHS) is a very rare autosomal recessive disorder which presents withrepeated bacterial infections, albinism, progressive peripheral neuropathy, cranial nerve abnormalities andpatients have characteristic silvery grey hair and giant bluish grey granules in cytoplasm of white blood cells.Late stages presents with accelerated phase of this disease which is characterized by lymphohistiocytic infiltrationof spleen, liver and lymph nodes. Here, we report a case of one year old child who presented to us in acceleratedphase of CHS and diagnosis was made on clinical characteristic findings and presence of largeazurophilicgranules in granulocytes and lymphocytes in peripheral blood smear and bone marrow